Small Side Games Terhadap Peningkatan Kebugaran Jasmani Peserta Ekstrakurikuler Sepakbola SMPN 2 Cilamaya Kulon - Kasanudin Kasan; Resty Gustiawati; Bambang Ismaya (Universitas Singaperbangsa, 2020)
This study aims to determine the physical fitness of extracurricular football participants in SMPN 2 Cilamaya Kulon, Karawang. During training and competition, the participants easily feel tired and their concentration decreases. Consequently, training becomes less effective. Even the extracurricular participant who have good techniques still have poor physical fitness. From this problem, the researchers conducted an experiment to improve the physical fitness of football extracurricular participants in SMPN 2 Cilamaya Kulon, Karawang. Experimental research using a one-group pretest-posttest design was used in this study. This study used purposive sampling with a sample of 20 participants. The result of this study using a small-side game exercise model revealed that there was a significant effect on the physical fitness of football extracurricular participants. It can significantly see from the result obtained in the calculation of tcount (9.47)> ttable (2.09). This calculation means that the hypothesis (Ho) was rejected at the significance level ɑ = 0.0. Thus, the small-side game exercise method affected on physical fitness of extracurricular football participants in SMPN 2 Cilamaya Kulon, Karawang. Keywords: physical fitness, small-side game, football, extracurricular